Adobe Photoshop Lightroom Classic - Concepcion, Rafael (Classroom in a book., 2022)
Learn proven methods to keep your photography archive organized. Leverage tools in each module to reduce the amount of time you spend working on images. Take advantage of ground-breaking changes to AI-based masking to select skies, subjects, color ranges, and tones, making hours of editing turn into minutes. Experiment with color grading tools to pull the best out of all of the elements in your images. Create stylish books and print layouts, dynamic slideshows, and interactive web galleries to showcase your images. Access collections and presets on your desktop, mobile device, or on the web! The fastest, easiest, most comprehensive way to learn Adobe Photoshop Classroom in a Book®, the best-selling series of hands-on software training workbooks, offers what no other book or training program doesan official training series from Adobe, developed with the support of Adobe product experts. Adobe Photoshop Lightroom Classic Classroom in a Book (2022 release) contains 11 lessons that cover the basics and beyond, providing countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you. Purchasing this book includes valuable online extras. Follow the instructions in the book's "Getting Started" section to unlock access to: Downloadable lesson files you need to work through the projects in the book Web Edition containing the complete text of the book, interactive quizzes, and videos that walk you through the lessons step by step What you need to use this book: Adobe Photoshop Lightroom Classic (2022 release) software, for either Windows or macOS. (Software not included.) Note: Classroom in a Book does not replace the documentation, support, updates, or any other benefits of being a registered owner of Adobe Photoshop Lightroom Classic software.